Modular finger and hand motion capturing system based on inertial and magnetic sensors - Valtin, Markus; Salchow, Christina; Seel, Thomas; Laidig, Daniel; Schauer, Thomas (Current Directions in Biomedical Engineering, 2017)
The assessment of hand posture and kinematics is increasingly important in various fields. This includes the rehabilitation of stroke survivors with restricted hand function. This paper presents a modular, ambulatory measurement system for the assement of the remaining hand function and for closed-loop controlled therapy. The device is based on inertial sensors and utilizes up to five interchangeable sensor strips to achieve modularity and to simplify the sensor attachment. We introduce the modular hardware design and describe algorithms used to calculate the joint angles. Measurements with two experimental setups demonstrate the feasibility and the potential of such a tracking device.
CRIS-Team Scopus Importer:2021-03-31
Keywords: Finger kinematics; Hand; Human motion analysis; Inertial measurement units; Joint angle estimation